Remediation of petroleum contaminated soils : biological, physical, and chemical processes - Riser-Roberts, Eve (Lewis Publishers, 1998)
Remediation of Petroleum Contaminated Soils: Biological, Physical, and Chemical Processes provides exceptional coverage of information essential for the remediation of soils contaminated by petroleum products. Every aspect of in situ and ex situ bioremediation is discussed. Chemical and physical processes in current use are presented. Not only are the processes for treating the contaminated soils described, but also those for dealing with contaminated leachates and volatile organic compounds (VOCs) resulting from the contamination incident or from the treatment processes themselves.